Mr.Vc v2: An updated version of database with increased data of transcriptome and experimental validated interactions - Zhang, Zhiyuan; Chen, Guozhong; Hussain, Wajid; Qin, Zixin; Liu, Juntong; Su, Yang; Zhang, Hao; Ye, Mingquan (Frontiers in Microbiology, 2022)
Mr.Vc is a database of curated Vibrio cholerae transcriptome data and annotated information. The main objective is to facilitate the accessibility and reusability of the rapidly growing Vibrio cholerae omics data and relevant annotation. To achieve these goals, we performed manual curation on the transcriptome data and organized the datasets in an experiment-centric manner. Mr.Vc v2, which is significantly increased from the previous version, contains 107 microarray experiments, 106 RNA-seq experiments, and 3 Tn-seq projects, covering 56,839 entries of DEGs (Differentially Expressed Genes) from transcriptomes and 7,463 related genes from Tn-seq, respectively. Users can obtain all DEGs of this experiment while searching for an interesting experiment in Mr.Vc v2. For Vibrio cholerae operon annotation, 79 unknown operons annotated through text-mining analysis that would provide more clues about how Vibrio cholerae modulates gene regulation. Meanwhile, to understand the relationship between genes or experiments, we performed gene co-expression analysis and experiment-experiment correlation analysis. A total of 270,129 gene co-expression entries and 11,990 entries of experiment-experiment correlation was obtained. In additional, functional module named “Interactions” which dedicates to collecting experimentally validated interactions about Vibrio cholerae from public databases, MEDLINE documents and literature in life science journals, in total 1,316 entries of interactions were collected, including 496 protein-chemical signaling molecule interactions, 472 protein-protein interactions, 306 TF (Transcription Factor)-gene interactions and 42 Vibrio cholerae-virus interactions, most of which obtained from 402 literature through text-mining analysis. We manually validated these interactions to ensure quality and credibility. To make the information easier to access, Mr.Vc v2 is equipped with a search widget, enabling users to query what they are interested in. Mr.Vc v2 is freely available at http://mrvcv2.biownmc.info.